Enhancing Hydrophobicity in Polyester Fabrics: The Role of PDMS and Silica in Surface Treatment - Paulo Romano Correia; Débora Leal; Vinícius Oliveira; Eduardo Kerche; Rodrigo Polkowski (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
Superhydrophobic fabrics play a key role in sustainable industrial applications, including oil/water separation and self-cleaning materials. This study addresses the challenge of enhancing hydrophobicity while preserving fabric functionality by modifying its surface via dip-coating with poly(dimethylsiloxane) (PDMS) and silica nanoparticles. Water contact angle (WCA) measurements were performed by depositing droplets on the fabric surface and capturing images via optical microscopy. The angles were determined using the tangent method in the ImageJ software. Eight measurements were taken per sample to ensure reproducibility. Untreated fabric exhibited a WCA of 84°, while PDMS coatings (2 wt% and 4 wt%) increased WCAs to 129.1° and 131.7°, respectively. The incorporation of silica nanoparticles further enhanced hydrophobicity (WCA: 137°), attributed to the increased roughness on the surface observed by optical microscopy (OM). However, higher PDMS concentrations (4 wt%) reduced fabric permeability, compromising the fluid flow. These results underscore the need for PDMS’s content optimization to maintain breathability while achieving robust water repellency.